2019
DOI: 10.1096/fj.201902318r
|View full text |Cite
|
Sign up to set email alerts
|

RAD50 regulates mitotic progression independent of DNA repair functions

Abstract: The Mre11A/RAD50/NBN complex (MRN) is an essential regulator of the cellular damage response after DNA double‐strand breaks (DSBs). More recent work has indicated that MRN may also impact on the duration of mitosis. We show here that RAD50‐deficient fibroblasts exhibit a marked delay in mitotic progression that can be rescued by lentiviral transduction of RAD50. The delay was observed throughout all mitotic phases in live cell imaging using GFP‐labeled H2B as a fluorescent marker. In complementation assays wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Rad50, which is not found among the high-scoring interaction proteins, is a key component of the Mre11-Rad50-Nbs1 (MRN) complex involved in DNA double-strand break repair. Although RAD50 is reported to regulate mitotic progression independent of DNA repair functions, it is preferentially colocalized with chromosomes rather than centrosomes, spindle poles, or spindles, which more directly affect the assembly of cell division (54). Considering that SIRT2 is localized on the mitotic spindles and spindle pole from prophase until telophase, SIRT2 is colocalized with SMC1A but not RAD50 in mitosis.…”
Section: Discussionmentioning
confidence: 94%
“…Rad50, which is not found among the high-scoring interaction proteins, is a key component of the Mre11-Rad50-Nbs1 (MRN) complex involved in DNA double-strand break repair. Although RAD50 is reported to regulate mitotic progression independent of DNA repair functions, it is preferentially colocalized with chromosomes rather than centrosomes, spindle poles, or spindles, which more directly affect the assembly of cell division (54). Considering that SIRT2 is localized on the mitotic spindles and spindle pole from prophase until telophase, SIRT2 is colocalized with SMC1A but not RAD50 in mitosis.…”
Section: Discussionmentioning
confidence: 94%
“…Typical marker genes of oogenesis, such as gdf9 and dnd1 ( Liu and Ge, 2007 ; Yang et al, 2012 ), were widely expressed in the three identified germ cell types. Dazl ( Bachvarova et al, 2004 ; Li et al, 2016 ; Bertho et al, 2021 ) was highly expressed in early oogonia, while the mitotic marker rad50 ( Kostyrko et al, 2015 ; Völkening et al, 2020 ; Liu et al, 2021 ) was mainly expressed in mitotic oogonia ( Figure 1D ). In addition, we identified somatic cells based on the following markers: follicle cells ( foxl2 , amh and hsd17b1 ) ( Pisarska et al, 2011 ; Luo et al, 2020 ; Moolhuijsen and Visser, 2020 ; Li et al, 2021 ), endothelial cells ( fli1 and fn1a ) ( Nagai et al, 2018 ; Wu et al, 2021 ), T cells ( cd2 , cd247 and cd28 ) ( Hurley et al, 1994 ; Lundholm et al, 2010 ), macrophages ( cd68 , epx and mmp9 ) ( Hunyady et al, 1996 ; Sendler et al, 2018 ) and erythrocytes ( alas2 ) ( Munday et al, 2000 ; Tsang et al, 2017 ) ( Figure 1E ).…”
Section: Resultsmentioning
confidence: 99%
“…As the progression of cancer selects for advantageous mutations [133], disruption of some MRE11 conserved residues might not be beneficial. Supporting this, there is evidence that these three genes may also have independent functions [125,134]. Thus, some components of the MRN complex may be more critical for DSB repair than others.…”
Section: Discussionmentioning
confidence: 88%